2001
DOI: 10.1017/s1350482701001098
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of Meteosat rainfall estimation techniques in Kenya

Abstract: Two methods for estimating ten‐day rainfall totals from Meteosat infra‐red imagery were compared for the April–June 1996 ‘long rains’ of Kenya in an area covering the eastern highlands and the Tana and Athi river basins. One of these (the Bristol ‘B4’ method) was then used for rainfall estimation for the whole of Kenya, for November 1996 and the other, the TAMSAT ‘Cold Cloud Duration’ (CCD) method was used to estimate rainfall for the whole of Kenya for November 1997 to April 1998. April–June 1996 was an unusu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Given the heterogeneous nature of the African rainfall climate, CCD fields are regionally calibrated assuming a linear relationship between CCD and rainfall for each calendar month using historic gauge measurements, ensuring the resulting estimates reflect the expected local conditions [17][18][19]. The TAMSAT method has shown high levels of skill across Africa [8,10,35,[39][40][41][42].…”
Section: The Tamsat Methodsmentioning
confidence: 99%
“…Given the heterogeneous nature of the African rainfall climate, CCD fields are regionally calibrated assuming a linear relationship between CCD and rainfall for each calendar month using historic gauge measurements, ensuring the resulting estimates reflect the expected local conditions [17][18][19]. The TAMSAT method has shown high levels of skill across Africa [8,10,35,[39][40][41][42].…”
Section: The Tamsat Methodsmentioning
confidence: 99%
“…Comparisons with other available products have been carried out, including for Kenya (Herman et al 1997;Tucker and Sear 2001), West Africa (Laurent et al 1998;Jobard et al 2011;Snijders 1991), Ethiopia (Dinku et al 2007), southern Africa (Thorne et al 2001), and Uganda (Asadullah et al 2008;Maidment et al 2013). These showed that the TAMSAT approach outperforms or is comparable to other available satellite-based datasets with similar spatial and temporal resolution and extent.…”
Section: Introductionmentioning
confidence: 99%
“…Although few, some studies have been performed at the country scale to evaluate satellite rainfall products. In Africa, these studies include Angola (Pombo, de Oliveira, and Mendes 2015), Ethiopia and Zimbabwe (Dinku et al 2007;Diro et al 2009;Hirpa, Gebremichael, and Hopson 2010), Kenya (Tucker and Sear 2001), Mozambique (Toté et al 2015), and Uganda (Asadullah, McIntyre, and Kigobe 2008;Maidment et al 2013). None of these studies was carried out for a West African country.…”
Section: Introductionmentioning
confidence: 99%